Psychogenic Needs of Affection in Novel "Warm Bodies" by Isaac Marion: A Psychological Approach - Aditya Zadira; Gaguk Rudianto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This Research aims is to analyze and describe the form of Psychogenic needs of affection the needs of affection of the main character in “Warm Bodies” novel by Isaac Marion. In this research, researcher uses the Needs of Affection theory of Henry Murray. In the research design, researcher uses descriptive qualitative research, the primarily data is the Novel Warm Bodies by Isaac Marion which was published in 2011. The researcher uses Non-participatory observation as method of collecting the data. The researcher uses categorization data as the method of analyzing data. The researcher found the data all form the main character of the novel needs of affection based on experienced by main characters which are involved R and Julie. There are form of Psychogenic needs of affection such as need of affiliation found 3 data, need of rejection found 2 data, need of succorance found 2 data, need of nurturance 2 data and need of play found 1 data.